Rhinoceromyia, a peculiar new genus of long-legged flies from Guinea (Diptera: Dolichopodidae: Dolichopodinae) - Grichanov, Igor Ya. (Zootaxa, 2024)
The genus Rhinoceromyia Grichanov gen. nov. is described from the tropical forest of southeastern Guinea to accommodate a new species, Rhinoceromyia dubrovskii Grichanov sp. nov. with a peculiar horn on the male face, a very unusual character in the Empidoidea. The secondary segmentation and articulation of the male cercus is also an extraordinary character in the Dolichopodidae. The new genus is placed in the subfamily Dolichopodinae and is considered close to the Afrotropical genus Afropelastoneurus Grichanov, differing from the latter in remarkable characters of head, wing and male genitalia.